Mon crime = The crime is mine [videorecording (DVD)] - Ozon, François, 1967-; Tereszkiewicz, Nadia, 1996-; Marder, Rebecca, 1995-; Huppert, Isabelle; Luchini, Fabrice, 1951-; Boon, Dany; Dussollier, André; Sulpice, Edouard; Laspalès, Régis, 1957-; Prévost, Daniel; Lefebvre, Félix; Buyle, Evelyne, 1948 or 1951-; et al. (Music Box Films, 2024)
After a struggling actress stands trial for the murder of a lascivious producer in 1930s Paris, she ascends to scandalous stardom with her lawyer roommate. A new life of fame, wealth, and tabloid celebrity awaits, until the truth comes out.